Estimates of exploitation rates of the spiny lobster fishery for Panulirus argus from tagging within the Bahía Espíritu Santa 'Sian Ka'an' Biosphere Reserve, Mexican Caribbean - Ley-Cooper, K.; de Lestang, S.; Phillips, Bruce; Lozano-Alvarez, E. (Taylor & Francis, 2012)
The Caribbean spiny lobster (Panulirus argus) fishery is currently being assessed for a certification process. It is the main economic activity within the Biosphere Reserve of Sian Ka'an-Mexico (SK), which is a marine-protected area where restricted access fishing is allowed. In this study, commercial catch rates were examined, and lobsters over a wide size range were tagged throughout the 2010/2011 fishing season, to assess fishing mortality rates and movement patterns in Bahía Espíritu Santo-SK. Lobster tag recovery data were aggregated into 2-week periods and analysed using a modified Brownie model that was parameterized to account for lobster tag-reporting, and the lobster tag-retention rates. This allowed the estimation of instantaneous rates of natural and fishing mortality, considering catchability and fishing effort. Independent aquaria trials were conducted to better estimate lobster tag retention, tagging-induced mortality and interviews with fishermen were conducted to better estimate lobster tag reporting. Based mainly on legal-sized juveniles with fast growth rates found in casitas, the stock is subject to fishing to a maximum depth of 20 m, because of the prohibition of SCUBA diving and the use of other fishing gear. The Brownie model indicated that exploitation rates within this bay area were high,>0.94. Changes in catch per unit of effort and catchability throughout the season explain how the ‘casita/campo’ system allows for a seasonal replenishment of juveniles and adults, which has kept the landings relatively stable for the past decade.